Eeg Beta Band Frequency Domain Evaluation for Assessing Stress and Anxiety in Resting, Eyes Closed, Basal Conditions - Canete-Arratia, L; Diaz-Munoz, H (Elsevier B.V., 2019)
The study presents a frequency domain, instead of a relative power intensity comparison framework domain, that evaluates the degree of anxiety and stress brain network activated in high beta oscillation (22-30 Hz), during a resting, EC basal condition of EEG recording. The parameter measured served as an evaluator of the brain spontaneous, self-generated, global de-synchronizing, workload endogenous attractors that displace the EEG oscillatory dynamics toward free energy-consuming processing loops. The distinction of the high beta EEG waves as related with stress and anxiety, together with an approach based primarily on the inter-channel frequency correlation, rather than only the power activation of the frequency beta range, allowed us to supplement with new finding and ways to evaluate the impact of self-generated processing attractors that kept our brain apart from natural tendency to re-synchronize, save and reorganize energy. © 2020 The Authors. Published by Elsevier B.V.